2009
DOI: 10.1063/1.3210774
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the loads on a cylinder undergoing harmonic in-line motion

Abstract: We use the finite-difference computational fluid dynamics method to study in detail the flow field around a circular cylinder in a uniform stream while undergoing in-line harmonic motion. For a given motion amplitude, there exists a critical forcing frequency below which the lift and drag can be period-n, quasiperiodic, or chaotic. Similarly, for a given frequency, there exists a critical amplitude below which the lift and drag can be period-n, quasiperiodic, or chaotic. Above these critical conditions, the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 26 publications
(28 reference statements)
2
6
0
Order By: Relevance
“…This indicates that the fluid force acts in phase with the cylinder displacement and the inertial force acting on it (i.e. the d'Alembert force, À m € x), in agreement with the results of Nishihara et al (2005) and Marzouk and Nayfeh (2009). The magnitude of the energy transferred to the cylinder is proportional to jC D j sin ϕ (Khalak and Williamson, 1999).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This indicates that the fluid force acts in phase with the cylinder displacement and the inertial force acting on it (i.e. the d'Alembert force, À m € x), in agreement with the results of Nishihara et al (2005) and Marzouk and Nayfeh (2009). The magnitude of the energy transferred to the cylinder is proportional to jC D j sin ϕ (Khalak and Williamson, 1999).…”
Section: Resultssupporting
confidence: 86%
“…Nishihara et al (2005) also observed large amplitude fluctuating drag forces acting on a cylinder undergoing forced streamwise vibrations (A/D ¼0.05) at low values of U r St=f à . This was also observed in the numerical simulations of Marzouk and Nayfeh (2009). By decomposing the signal into components in phase with the cylinder displacement and velocity, they showed that the large amplitude drag was caused by an increase in the inertial forces associated with the cylinder motion.…”
Section: Resultssupporting
confidence: 56%
“…Some distinct modes of synchronisation have been observed in the wake of a controlledoscillatory circular cylinder over a range of Reynolds numbers, Re = U ∞ D/ν, where U ∞ is the free stream velocity, D is the cylinder diameter, and ν is the kinematic viscosity. Published works in this respect include a cylinder undergoing one-degree-of-freedom (1-dof) sinusoidal vibration either in the transverse direction to the incident flow (Bishop & Hassan 1964;Koopmann 1967;Griffin & Ramberg 1974;Stansby 1976;Williamson & Roshko 1988;Ongoren & Rockwell 1988a;Anagnostopoulos 2000;Carberry, Sheridan & Rockwell 2005;Leontini et al 2006;Morse & Williamson 2009), or in the incident flow direction (Tanida, Okajima & Watanabe 1973;Griffin & Ramberg 1976;Sarpkaya, Bakmis & Storm 1984;Mittal et al 1991;Zdravkovich 1996;Cetiner & Rockwell 2001;Xu, Zhou & Wang 2006;Al-Mdallal, Lawrence & Kocabiyik 2007;Marzouk & Nayfeh 2009). Commonly, f s /f d synchronises to N or 1/N (where N is an integer number) when f d is respectively close to the superharmonics (Nf St ) or subharmonics (f St /N) of the Strouhal number (Ongoren & Rockwell 1988a;Konstantinidis & Bouris 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This analogy concerns both the modes of vortex formation and frequency selection in the the wake of circular cylinders. For instance, it is now well acknowledged that with the increasing amplitude of global symmetric perturbations, these will eventually dominate over a large portion of the flow domain around a circular cylinder, thereby suppressing lift fluctuations [27,43,46,118,119]. Similar effects have also been observed with symmetric local forcing by a single synthetic jet located at either the front or back stagnation point, or a pair of symmetrically placed synthetic jet operated in-phase [89,108,112,[120][121][122][123].…”
Section: Discussionmentioning
confidence: 67%
“…In the former case, the perturbation in the relative velocity between the body surface and the oncoming free stream is 'uniform' throughout the flow. For nominally two-dimensional flows around a circular cylinder placed in a free stream, global perturbation methods include oscillations of the cylinder in-line with the free stream [25][26][27][28][29] or transverse to the free stream [30][31][32][33][34], rotational oscillations of the cylinder [35][36][37][38], combinations of these types of cylinder oscillations [39][40][41][42], and superposition of sound waves or fluid pulsations on the free stream [18,[43][44][45][46][47][48][49][50][51]. In principle, imposing global perturbations provides a means to modify the process of vortex formation and the shedding frequency, as well as other flow characteristics shown in numerous related studies including those cited above.…”
Section: Flow Control Definitions and Preliminary Remarksmentioning
confidence: 99%